Distribution of absorbed dose by the perimeter and the length of the polymeric protective sheath at radiacinous irradiation of the ship cable - Bezprozvannych, G.V.; Mirchuk, I.A. (Вопросы атомной науки и техники, 2019)
The research of the distribution of the absorbed dose along the perimeter and length of the polymer protective sheath on the basis of a halogen-free composition depending on the technological dose of radiation exposure of shipboard cable samples was performed. It has been established that irregularity of irradiation around the cable perimeter can reach 20…30% with a technological dose in the range of 1.25…0.5. The irradiation along the cable is more uniform and does not exceed 5% at a technological dose in the range of 1.25…0.567. With a reduction in the technological dose, the irregularity of radiation around the perimeter and length of the cable increases. It is established that with an average absorbed dose of 210 kGy, the protective polymer shell does not meet the requirements of the standard for relative elongation at break. Optimal and physical-mechanical characteristics of the polymer shell made of halogen-free material are provided under irradiation in the range of the absorbed dose of 160 to 170 kGy.